2022
DOI: 10.1111/sum.12798
|View full text |Cite
|
Sign up to set email alerts
|

Conservation agriculture practice influences soil organic carbon pools in intensive rice‐based systems of the Eastern Indo‐Gangetic Plain

Abstract: Studies of rice‐based systems in the Indo‐Gangetic Plain (IGP) have demonstrated the beneficial effects of Conservation Agriculture on soil organic carbon (SOC) status, along with increased soil health and crop productivity. However, it remains unclear as to the time for such treatments to have a positive effect. In this study of lentil‐mung bean‐rice and wheat‐mung‐rice rotations in Bangladesh positive effects of strip planting or bed planting, along with residue return, on SOC pools were apparent after 1.5 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
(71 reference statements)
1
5
0
Order By: Relevance
“…Other reasons for the gradual increase in yield for the cool season crops with CA may be related to the build-up of soil organic matter. In the present experiments, we also confirmed the increased yield in SP and HR was associated with the improvement of soil physical properties, soil organic carbon and N levels under CA practices (Islam, 2017;Islam et al, 2022). Several other studies in the IGP demonstrated that improvements in soil physical properties, soil organic carbon, N and other nutrients increased crop yields under CA systems (Das et al, 2013;Das et al, 2014;Salahin et al, 2021).…”
Section: Factors Affecting Response To Conservation Agriculturesupporting
confidence: 88%
See 1 more Smart Citation
“…Other reasons for the gradual increase in yield for the cool season crops with CA may be related to the build-up of soil organic matter. In the present experiments, we also confirmed the increased yield in SP and HR was associated with the improvement of soil physical properties, soil organic carbon and N levels under CA practices (Islam, 2017;Islam et al, 2022). Several other studies in the IGP demonstrated that improvements in soil physical properties, soil organic carbon, N and other nutrients increased crop yields under CA systems (Das et al, 2013;Das et al, 2014;Salahin et al, 2021).…”
Section: Factors Affecting Response To Conservation Agriculturesupporting
confidence: 88%
“…)mung bean (Vigna radiata (L.) R. Wilczek)monsoon rice (Oryza sativa L.) and a cereal-dominated system: wheat (Triticum aestivum L.)mung beanmonsoon rice, were evaluated in the current study. Full details of the sites and study are reported by Islam et al (2022) and Islam (2017), and in Supplementary materials (Methods S1 and S2,and Tables S1 to S5). Only pertinent details are provided in the body of this article.…”
Section: Methodsmentioning
confidence: 99%
“…Recent attempts have been made to reduce organic carbon loss from soils for climate change mitigation, whose measures include crop residue incorporation (Lupwayi et al 2022;Zhu et al 2022a), organic matter stabilization with clay and metal oxides (Baumann et al 2022;Di et al 2022), fertilizer application (da Silva et al 2022;Gasser et al 2022;Qiu et al 2022;Thakur et al 2022;Zhang et al 2022b), reduced or conservational tillage (Ferrara et al 2022;He et al 2022a;Islam et al 2022), rotational grazing (Abdalla et al 2022;Dong et al 2021), silvopastoral system (Aryal et al 2019;Valenzuela Que et al 2022), and ecological restoration (Howson et al 2022;Wang et al 2020b;Zhao et al 2022). Among them, application of biochar is a promising one due to simultaneous achievement of waste management, nutrient delivery, contaminant immobilization, and climate change mitigation.…”
Section: Co 2 Emissionsmentioning
confidence: 99%
“…Differences in SOC and labile-C changes between crop rotation systems can be owing to the different quantity and quality of returned crop residues. For example, high levels of root biomass production in the cereal-dominated rotation systems (here cornwheat crop rotation system) with the above content of lessdecomposable cellulose in their residues and high C/N ratio may contribute to a remarkable quantity of SOC over time (Ghosh et al, 2016;Islam et al, 2022). In addition, improvement of SOC and labile-C through the inclusion of legumes (B-W; in this study mung bean) in the rotation with wheat might be attributable to an increase in the rate of residue decomposition (i.e., the C/N ratios of involved crops).…”
Section: Impact Of Weather Variation and Crop Rotation System On Soc ...mentioning
confidence: 99%